Genome-wide UPD screening in patients with intellectual disability - Schroeder, Christopher Maximilian; Ekici, Arif Bülent; Moog, Ute; Grasshoff, Ute; Mau-Holzmann, Ulrike; Sturm, Marc; Vosseler, Vanessa; Poths, Sven; Rappold, Gudrun; Riess, Angelika; Riess, Olaf; Dufke, Andreas; et al. (European journal of human genetics, 2014)
Uniparental disomy (UPD) describes the inheritance of a pair of chromosomes from only one parent. It may occur as isodisomy, heterodisomy or a combination of both and may involve only chromosome segments. UPD can affect each chromosome. The incidence is estimated to be around 1:3500 in live births. Some parts of chromosomes are subject to ‘parent-of-origin imprinting’ and the phenotypic effect in UPD syndromes is mainly due to functional imbalance of imprinted genes. Isodisomy can result in mutation homozygosity in autosomal-recessive inherited diseases. UPD causes several well-defined imprinting syndromes associated with intellectual disability (ID). Although knowledge on frequency and size of UPDs in patients with unexplained ID remains largely unknown as no efficient genome-wide screening technique was available for detection of both isodisomic and heterodisomic UPDs. SNP microarrays have been proven to be capable to detect UPDs through Mendelian errors. The correct subclassification of UPD requires child-parent trio experiments. To further elucidate the role of UPD in patients with unexplained ID, we analyzed a total of 322 child-parent trios. We were not able to detect UPDs (isodisomies and heterodisomies) within our cohort spanning whole chromosomes or chromosomal segments. We conclude that UPD is rare in patients with unexplained ID.